Basic measurements of radiation at station Minamitorishima (2010-04 et seq) - Shun Sasaki; Kohshiro Dehara; Osamu Ijima; Kazumasa Matsuzawa; Kouichi Nakashima; Jun Ohtake; Masao Omori; Matsumi Takano; Hiroshi Tatsumi (PANGAEA, 2024)
This is a compilation of all radiation datasets from Minamitorishima station that were published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).